Implementasi Kebijakan Pembuatan Kartu Tanda Penduduk Elektronik di Dinas Kependudukan dan Catatan Sipil Kabupaten Malinau - Loris; Muhlis Hafel; Darmanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The implementation of the electronic identity card (KTP-el) is part of an effort to accelerate and support the accuracy of the population data base in the district/city, province and national population data base. This research aims to analyze the implementation of the electronic identity card policy at the Population and Civil Registration Office of Malinau Regency and analyze the factors that support and hinder the implementation of the electronic identity card policy program at the Population and Civil Registration Office of Malinau Regency. This research was conducted using descriptive qualitative methods. The results showed that the Implementation of the Electronic Identity Card (KTP-el) Policy at the Population and Civil Registration Office of Malinau Regency has gone well. However, there are still obstacles in the process of recording and printing KTP-el that need to be overcome. There needs to be additional training and technical guidance to improve the knowledge of the apparatus in carrying out the system and policies that have been set.